1984
DOI: 10.1016/0035-9203(84)90032-4
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and characterization of hydatid fluid antigens with identification of an antigen similar to human serum albumin

Abstract: Human and sheep hydatid fluids were separated by ultrafiltration, gel chromatography and immunoabsorption into several immunogenic fractions in which both parasite antigens and host substances were present. The immunological characterization of proteic antigens was carried out by immunodiffusion and immunoelectrophoresis with rabbit and ram antisera. A line of identity was observed between a human fraction (labelled as III) and a sheep fraction (labelled as 2B). Further evidence of the presence of a parasitic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Cross-reactivity has been reported in infections by E. multilocularis, E. vogeli (1), Taenia saginata (2-7), Taenia solium (5,(8)(9)(10), Hymenolepis nana (10), Ascaris lumbricoides (3), Trichinella (11), Fasciola (8,11), Giardia lamblia (5), Toxoplasma gondii (5), Plasmodium falciparum (5), and Leishmania (4). Furthermore, bacterial infections, such as tuberculosis (8), and host antigens, such as seroalbumin (12,13) and red blood cells (14)(15)(16), are sources of false-positive results in hydatidosis serological tests.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactivity has been reported in infections by E. multilocularis, E. vogeli (1), Taenia saginata (2-7), Taenia solium (5,(8)(9)(10), Hymenolepis nana (10), Ascaris lumbricoides (3), Trichinella (11), Fasciola (8,11), Giardia lamblia (5), Toxoplasma gondii (5), Plasmodium falciparum (5), and Leishmania (4). Furthermore, bacterial infections, such as tuberculosis (8), and host antigens, such as seroalbumin (12,13) and red blood cells (14)(15)(16), are sources of false-positive results in hydatidosis serological tests.…”
Section: Introductionmentioning
confidence: 99%
“…The laminated layer is a protein‐carbohydrate‐lipid complex primarily containing the sugars glucosamine and galactosamine (1–3). It grows along with the parasite, increasing in thickness with age, and is permeable to host material such as immunoglobulins which have been found in the hydatid cyst fluid (4–8). The laminated layer appears to have two major functions: (i) to provide mechanical support to the fluid filled cyst and (ii) forming a barrier to protect the living part of the cyst from aspects of the cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the poor sensitivities of several antibody detection assays has been postulated to be due to the antibodies being 'mopped up' by high concentrations of circulating free antigen resulting in the formation of immune-complexes and rendering antibodies unavailable for detection [16]. The poor specificity has been attributed to cross-reactions between hydatid cyst fluid antigens and antigens of other related helminths [2,3,6,8,20] or with contaminant host proteins [3,21]. The host could be a high, moderate or low responder.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that a significant number of low antibody responders in hydatidosis may account for a low degree of sensitivity. The poor specificity has been attributed to cross-reactions between hydatid cyst fluid antigens and antigens of other related helminths [2,3,6,8,20] or with contaminant host proteins [3,21]. Thus, to improve the sensitivity and specificity of the serological test, the identification of hydatid specific antigen is of prime importance.…”
Section: Discussionmentioning
confidence: 99%